THE ROLE OF KNOWLEDGE MANAGEMENT AND SUSTAINABLE COMPETITIVE ADVANTAGE - Kusuma, Emeralda Ayu; Widiartob, Hermono; Efendi, David (Integrated Journal of Business and Economics (IJBE), 2021)
This study aims to determine the effect of knowledge management and competitive advantage on the performance of batik craftsmen in Kampoeng Jetis, Sidoarjo Regency. This study used a questionnaire by analyzing data from 30 respondents. Data were analyzed using SPSS in analyzing the validity and reliability test, classical assumption test and hypothesis testing. The results showed that knowledge management and competitive advantage had an effect on the performance of craftsmen. The study is limited to Kampoeng Batik Jetis Sidoarjo and need to conduct similar study in other craftmen community and be adjusted to creative economy industry basis.